Challenges in the control of food and water-borne parasitoses in the Philippines - Belizario , Vicente Y. Jr.; Anastacio, Marilyn Benedith M.
In the past two to three decades, food and water-borne parasitoses have been considered to have a substantial impact on public health in Asia with the increasing numbers of cases despite economic growth and development. Illness due to contaminated food is perhaps the most widespread health problem, and it is an important cause of reduced economic productivity and quality of life of those infected. In the Philippines, a number of parasitic infections brought about by food and water contamination are present: schistosoniiasis, heterophyidiasis, paragonimiasis, echinostomiasis/artyfechi-nostomosis, taeniasis, and intestinal capillariasis among others. Water-borne protozoa including Entamoeba, Giardia, Blastocystis and coccidians continue to be important causes of diarrhea! diseases, and infected individuals may be asymptomatic carriers. Food-handlers may also contaminate food and water by inadequate hand washing practices of infected persons or carriers. Pollution, poverty, and population growth are the three principal determinants of the epidemiology and public health impact of food and water-borne parasitoses. Disease recognition by clinical practitioners, diagnosticians, and laboratory workers is also a major challenge in the control of these parasitoses, which signifies a need to further strengthen the diagnostic capability of health personnel especially in endemic areas. Moreover, the real challenges of a control center on health education and food safety since people contract most of these infections by eating raw, improperly prepared, or food contaminated with parasite infective stages. (Author)
In: Acta Medica Philippina, 2007 vol. 41 (1) pages: 54-58
Keywords: Parasitoses, Water-borne; Parasitoses, Food-borne